Heavy metal pollution and its relation to the malformation of green mussels cultured in Muara Kamal waters, Jakarta Bay, Indonesia. (August 2018) - Riani, Etty; Cordova, Muhammad Reza; Arifin, Zainal
Abstract: Jakarta Bay has become contaminated by both organic and inorganic pollutants, including heavy metals. This study aimed to examine the effect of heavy metal pollution on green mussels cultured in Muara Kamal Waters, Jakarta Bay over seven months. In this research, the water quality was assessed, through measuring the concentrations of the heavy metals, Hg, Pb, Cd, Cr, and Sn in the water, and in the tissue of green mussels that had been cultured there for seven months. The percentage of congenital abnormalities (malformations) in the green mussels was analyzed descriptively and the relationship between the water quality, heavy metals, and green mussel malformation was studied through principal component analysis (PCA). The result showed that the heavy metals concentrations in the water and sediment exceeded the quality standard at Muara Kamal but that in other respects the water quality was quite good. The green mussels cultured there for seven months had accumulated high concentrations of heavy metals, and ±60% of them had malformations of their shells. Based on the heavy metal concentrations in their bodies, the main cause of malformations in green mussels was suspected to be Pb, Hg, and Sn. However, the result of PCA showed it was the interaction between nitrogen compounds, phosphate, turbidity, salinity, pH, as well as the heavy metals in the water that determined the green mussel abnormality. Highlights: Muara Kamal water and sediment is polluted by heavy metals and organic materials. Concentrations of Hg, Cr 6+, Pb, Cd and Sn were exceeded the water quality standard. Organic fractions and low pH make heavy metals more bioavailable. Bioavailability and toxicity of the heavy metals absorbed by the mussels About 60% of cultured green mussel is reported having shells malformation.